The transmembrane proteins (TMEM) and their role in cell proliferation, migration, invasion, and epithelial-mesenchymal transition in cancer - Herrera-Quiterio, Gloria Angelina; Encarnación-Guevara, Sergio (Frontiers in Oncology, 2023)
Transmembrane proteins (TMEM) are located in the different biological membranes of the cell and have at least one passage through these cellular compartments. TMEM proteins carry out a wide variety of functions necessary to maintain cell homeostasis TMEM165 participates in glycosylation protein, TMEM88 in the development of cardiomyocytes, TMEM45A in epidermal keratinization, and TMEM74 regulating autophagy. However, for many TMEM proteins, their physiological function remains unknown. The role of these proteins is being recently investigated in cancer since transcriptomic and proteomic studies have revealed that exits differential expression of TMEM proteins in different neoplasms concerning cancer-free tissues. Among the cellular processes in which TMEM proteins have been involved in cancer are the promotion or suppression of cell proliferation, epithelial-mesenchymal transition, invasion, migration, intravasation/extravasation, metastasis, modulation of the immune response, and response to antineoplastic drugs. Inclusive data suggests that the participation of TMEM proteins in these cellular events could be carried out through involvement in different cell signaling pathways. However, the exact mechanisms not clear. This review shows a description of the involvement of TMEM proteins that promote or decrease cell proliferation, migration, and invasion in cancer cells, describes those TMEM proteins for which both a tumor suppressor and a tumor promoter role have been identified, depending on the type of cancer in which the protein is expressed. As well as some TMEM proteins involved in chemoresistance. A better characterization of these proteins is required to improve the understanding of the tumors in which their expression and function are altered; in addition to improving the understanding of the role of these proteins in cancer will show those TMEM proteins be potential candidates as biomarkers of response to chemotherapy or prognostic biomarkers or as potential therapeutic targets in cancer.